2011
DOI: 10.1007/s10886-011-9906-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Herbivory-induced Volatiles Among Cucumber (Cucumis sativus L.) Varieties has Consequences for the Attraction of Carnivorous Natural Enemies

Abstract: In response to herbivory by arthropods, plants emit herbivory-induced volatiles that attract carnivorous enemies of the inducing herbivores. Here, we compared the attractiveness of eight cucumber varieties (Cucumis sativus L.) to Phytoseiulus persimilis predatory mites after infestation of the plants with herbivorous spider mites (Tetranychus urticae) under greenhouse conditions. Attractiveness differed considerably, with the most attractive variety attracting twice as many predators as the least attractive va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 56 publications
(102 reference statements)
2
78
0
3
Order By: Relevance
“…Several cDNA contigs were identified as candidate sequences for volatile production based on high Pearson correlation coefficient (PCC) values between volatile emission data and gene expression data. Cucumber (E,E)-a-farnesene synthase and (E)-b-caryophyllene synthase were functionally characterized in vitro (Mercke et al, 2004).A recent study demonstrated that the volatile emission levels from infested cucumber leaves, including (E)-b-ocimene, (E,E)-4,8,12-trimethyltrideca-1,3,7,11-tetraene, and two other unknown compounds, correlated positively with the attraction of Phytoseiulus persimilis, a predatory mite species that targets herbivorous spider mites (Kappers et al, 2011). This result suggested that the VOCs can protect cucumber plants indirectly.…”
mentioning
confidence: 99%
“…Several cDNA contigs were identified as candidate sequences for volatile production based on high Pearson correlation coefficient (PCC) values between volatile emission data and gene expression data. Cucumber (E,E)-a-farnesene synthase and (E)-b-caryophyllene synthase were functionally characterized in vitro (Mercke et al, 2004).A recent study demonstrated that the volatile emission levels from infested cucumber leaves, including (E)-b-ocimene, (E,E)-4,8,12-trimethyltrideca-1,3,7,11-tetraene, and two other unknown compounds, correlated positively with the attraction of Phytoseiulus persimilis, a predatory mite species that targets herbivorous spider mites (Kappers et al, 2011). This result suggested that the VOCs can protect cucumber plants indirectly.…”
mentioning
confidence: 99%
“…Releasing these volatile compounds can improve plants' resistance to attacking herbivores, and an important aspect of defence is the ability to attract the herbivore's natural enemies such as predators and parasitoids (Mumm et al, 2008;Zakir, 2011;Kappers et al, 2011). Many herbivore-induced volatiles are terpenoids, the largest class of natural products (Dicke et al, 1990;Turlings et al, 1990;Dicke, 1994;Takabayashi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was similar to that described by Kappers et al (2011). Each aerial part was covered with an oven bag (48.26 cm x 23 cm x 1.27 cm; Reynolds, Richmond, CA, USA).…”
Section: Headspace Collectionmentioning
confidence: 99%
“…16 Os voláteis induzidos após o ataque dos herbívoros apresentam grande variabilidade e dependem da espécie de planta, 24 do herbívoro 25 e do seu instar ou estadio. 26 Também variam com o genótipo 27 e, neste caso, entre partes da planta e de acordo com o tempo, 28 considerado pelo período de 24 horas, uma vez que as emissões destes variam de dia e noite. 29 Isto facilita a mediação de interações da planta com insetos diurnos e noturnos.…”
Section: "Pedindo Ajuda": O Chamado Aos Inimigos Naturaisunclassified